Proyecto de factibilidad para la comercialización de zapatos para diabéticos marca Liwi en la ciudad de Loja - Espinosa Lara, Romel Javier (2015)
The overall objective of the present study is to determine the feasibility to create a marketer of shoes for diabetic Liwi brand and its marketing in the city of Loja, which used different methods and techniques, such as deductive, inductive scientific method and synthetic analytical and bibliographic collection, observation and survey respectively. In addition specific targets for the realization of this study based on the study of market, technical study, financial study and the financial evaluation were raised. The study of market held in the city of Loja, determined first sample, applying 359 surveys to diabetic patients to determine the demand for shoes for diabetics; and 197 surveys of businesses in the city that sell footwear for information and determine the offer was made. The results show a potential demand of 3521 diabetics, a real demand of 961 people with diabetes, an effective demand of 859 people with diabetes, the total supply is 192 pairs of shoes for diabetics and demand unsatisfied 667 shoes. The technical study, determined the installed capacity of the study which is in 667 pairs of shoe that can be traded, of which only use 89% of the installed capacity resulting in a capacity used 593 pairs of shoes for the first year. Determined the location of the study establishing a location in the central part of the city, settled the marketing service and material requirements process flows, equipment and personnel. Determined the organizational, administrative and legal structure of the company, which was its legal basis, the functional organizational structure of different levels, as well as charts and manual functions according to the needs of the company. In relation to the financial aspect, the study requires an investment of $13.731,95; which will be financed 27,18% with contributions from the owner of the project and the 72,82% remaining with a credit granted by the Bank of Loja, to 9.53% interest rate and 4 years term. The financial evaluation presents results that are favorable to the realization of the project: the VAN is $ 19.524,86; the TIR is 48,96%; the relation benefit - cost is 1,10 dollars; capital recovery period will be in 2 years, 8 months and 12 days; in the analysis of sensitivity values are less than one, therefore do not affect the project, to be changes as a 3,45% increase in costs and decrease of 3,10% in revenues. The conclusions and recommendations to the project significant is subsequently raise